A Pilot Study into an Integrated Special Needs Programme using CIPP Model - Mottan, Kannamah (Asian Journal of Assessment in Teaching and Learning, 2015)
This pilot study aimed to evaluate an integrated special needs programmes in a school from Penang. Direct observations and interviews with the teachers and the coordinator were conducted to corroborate the observations. The context, input, process, product (CIPP) evaluation model was applied to gather information mainly on the elements of the model on the performance of the programme. The results of the observations and the interviews with documents were checked against a check-list from Stufflebeam (2007). From the data recorded and observed it was seen that most of the criteria set for the model is adhered to.